Territorial development visions in Latin America: an analysis of spatial planning and land management legislations - SALAZAR GUAMÁN, Ximena (Utopía y Praxis Latinoamericana, 2024)
Spatial planning is positioned as a strategic public policy to articulate the spatial dimension within territorial development strategies in Latin America. This article aimed to examine the historical evolution and contemporary regulatory frameworks associated with territorial planning in the region, in order to characterize the visions of territorial development currently institutionalized. Through documentary analysis, a transition is identified from partial paradigms focused on economism, urbanism or environmentalism, towards systemic conceptions that seek to integrate the multiple territorial dimensions within a multidimensional approach. The objectives enshrined legally denote an emerging vision that aspires to sustainability, equity, institutionality and quality of territorial life. However, the implementation challenges are still substantial to effectively materialize this overcoming conception. Strengthened public capabilities and integrating visions genuinely incorporated into budget policy are required.